2011
DOI: 10.1155/2011/406812
|View full text |Cite
|
Sign up to set email alerts
|

Coral Bleaching Susceptibility Is Decreased following Short-Term (1–3 Year) Prior Temperature Exposure and Evolutionary History

Abstract: Coral exposed to short periods of temperature stress (≥1.0°C above mean monthly maximum) and/or increased frequencies of high temperatures may bolster resilience to global warming associated with climate change. We comparedMontastraea cavernosa(Linnaeus, 1767; Cnidaria, Scleractinia, Faviidae) from the Florida Keys National Marine Sanctuary (FKNMS) and the Flower Garden Banks National Marine Sanctuary (FGBNMS). Thermal stress has been reported frequently within the FKNMS; however, corals in the FGBNMS experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The question arose regarding whether this response was region-specific to the western Indo-Pacific, or the Great Barrier Reef. It is now known that the same cellular responses occur under the same conditions in the Caribbean species Montrastraea cavernosa and Millepora alcicornis [79]. These authors also found that bleaching susceptibility is decreased in coral and their symbionts when species have been exposed to prior bleaching events ( i.e.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The question arose regarding whether this response was region-specific to the western Indo-Pacific, or the Great Barrier Reef. It is now known that the same cellular responses occur under the same conditions in the Caribbean species Montrastraea cavernosa and Millepora alcicornis [79]. These authors also found that bleaching susceptibility is decreased in coral and their symbionts when species have been exposed to prior bleaching events ( i.e.…”
Section: Introductionmentioning
confidence: 82%
“…Many earlier studies focus on heat stress occurring over a temporal scale of weeks, including degree heating weeks (DHW [79]). This study reveals that expelled Symbiodinium cells in some corals, such as Sarcohphyton ehrenbergi , begin exhibiting signs of potentially reversible PCD after 9 hrs, and signs of irreversible PCD after 12 hrs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003). In addition, Haslun et al. (2011) suggested that corals that are exposed to frequent and short‐term temperature stress tend to be less temperature sensitive than those that are not exposed to such stress.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that coral hosts are affected less by seawater temperature stress over a short period of time through exaptation (Strychar & Sammarco 2008). Haslun et al. (2011) have also shown that corals that are exposed to frequent seawater temperature stress tend to be less temperature sensitive than those not exposed to such stress.…”
Section: Introductionmentioning
confidence: 99%